Phase variation mediated niche adaptation during prolonged experimental murine infection with Helicobacter pylori. - Salaün, L; Ayraud, S; Saunders, N (2005)
Changes in the repeats associated with the recently redefined repertoire of 31 phase-variable genes in Helicobacter pylori were investigated following murine gastric colonization for up to one year in three unrelated H. pylori strains. Between the beginning and end of the experimental period, changes were seen in ten genes (32 %), which would alter gene expression in one or more of the three strains studied. For those genes that showed repeat length changes at the longest time points, intermediate time points showed differences between the rates of change for different functional groups of genes. Genes most likely to be associated with immediate niche fitting changed most rapidly, including phospholipase A (pldA) and LPS biosynthetic genes. Other surface proteins, which may be under adaptive immune selection, changed more slowly. Restriction-modification genes showed no particular temporal pattern. The number of genes that phase varied during adaptation to the murine gastric environment correlated inversely with their relative fitness as previously determined in this murine model of colonization. This suggests a role for these genes in determining initial fitness for colonization as well as in subsequent niche adaptation. In addition, a coding tandem repeat within a phase-variable gene which does not control actual gene expression was also investigated. This repeat was found to vary in copy number during colonization. This suggests that changes in the structures encoded by tandem repeats may also play a role in altered protein functions and/or immune evasion during H. pylori colonization.